Utilizing medical thoracoscopy for the diagnosis of B‐cell lymphoma presenting with pleural effusion: A case series - Nai‐Chien Huan; Khai Lip Ng; Larry Ellee Nyanti; Jing Yi Khaw; Jiun Hang Lee; Nur Husna Mohd Aminudin; Dahziela Yunus; Nusaibah Azman; Maryam Ahmad Sharifuddin; Hema Yamini Ramarmuty; Kunji Kannan Sivaraman Kannan (Respirology Case Reports, 2024)
Abstract A third of patients with non‐Hodgkin's lymphoma (NHL) develop pleural effusion during the disease course for various reasons. In most cases, lymphoma‐related pleural effusion is a manifestation of widespread systemic disease, signifying a high tumour burden and therefore, a poorer prognosis. On the other hand, primary pleural lymphomas (PPLs) exhibit exclusive or dominant involvement of serous cavities, without detectable solid tumour masses. PPL is an uncommon disease and is of two types: primary effusion lymphoma (PEL) and diffuse large B‐cell lymphoma associated with chronic inflammation (DLBCL‐CI). PPLs not related to PELs and DLBCL‐CIs are exceedingly rare. Herein, we describe four patients with biopsy proven B‐cell NHL. One had no extra‐pleural involvement at the time of diagnosis, indicating PPL. In all cases, histopathological examination of pleural biopsies obtained via medical thoracoscopy (MT) were crucial in clinching the final diagnosis. Clinicians are alerted to the potential relationship between exudative effusion and NHL as well as the role of MT in the diagnosis of B‐cell NHL.